Investigation on the Role of Polypyrrole/Carbon Black Nanoparticles in the Electromechanical Behavior of Modified P(VDF-HFP). Issue 1 (4th May 2022) - Ardimas; Wattana, Puripat; Putson, Chatchai; Panse, Vishal R; Palupi, Endah Kinarya; Antarnusa, Ganesha; Basith, Abd; Fadli, Ulfa Mahfudli
Abstract: Recently, the polyvinylidenefluoride-co-hexafluoropropylene P(VDF-HFP) as electroactive polymers (EAPs) has been known to have great potentials in micro electro mechanical systems (MEMs) due to their light weight, low cost, and large electrical field-induced strain. In order to enhance their electromechanical properties, the modified P(VDF-HFP) with various conducting polymers such as polypyrrole (PPy) and carbon black (CB) is considerably required. In this work, the P(VDF-HFP) as matrix was doped with different loading of PPy/CB (< 1 wt%) and the composites films were obtained by using solution casting method. The influence of filler content on the dielectric properties and the conductivity of these thin films was investigated by using LCR meter. The maximum dielectric constant of the P(VDF-HFP)/PPy-CB was 2 times larger than the pure P(VDF-HFP) without conductive fillers. At low frequency, the both dielectric loss and conductivity were found to be slightly increased as consequence of the conducting polymers, but the conductive phase has not been achieved yet. In addition, a complete set of electromechanical properties were systemically explored using the result of strain displacement under the low electric field (< 5 MV/m). During the applied electric field, the average voltage peak-to-peak was attributed to the strain yield of approximately 0.08% at 2 MV/m. These observations indicate that the synergistic effect of conductive fillers induce their electric polarization and it can be considered as one of the promising candidates for actuator applications.